2021
DOI: 10.21153/jtlge2021vol12no2art1011
|View full text |Cite
|
Sign up to set email alerts
|

How individual experiential backgrounds are related to the development of employability among university students

Abstract: University students have different backgrounds and varied experiences. This diversity has frequently been examined with regard to performance in Higher Education. However, much less attention has been paid to its significance concerning employability. The investigation of this potential relationship is the focus of this study. In this research, 429 students at a German university were assessed on the strength of their employability, which here is defined as a multi-factorial construct. The Career Resources Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…A possible explanation for this can be that older students may already have established contacts, which makes them feel less need to establish new networks. Contrarily to what could be expected from previous research (Eimer & Bohndick, 2021;Erola et al, 2016), parental education did not correlate significantly with any of the career resources dimensions. A possible explanation for this lack of association can be that familiar background assumes a more expressive impact after work transition, when graduates are exposed to a less protective environment and when social and cultural capital plays a more determinant role in the way graduates navigate and adapt to the work world (Hirudayaraj, 2011;Tomlinson, 2017a).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A possible explanation for this can be that older students may already have established contacts, which makes them feel less need to establish new networks. Contrarily to what could be expected from previous research (Eimer & Bohndick, 2021;Erola et al, 2016), parental education did not correlate significantly with any of the career resources dimensions. A possible explanation for this lack of association can be that familiar background assumes a more expressive impact after work transition, when graduates are exposed to a less protective environment and when social and cultural capital plays a more determinant role in the way graduates navigate and adapt to the work world (Hirudayaraj, 2011;Tomlinson, 2017a).…”
Section: Discussionsupporting
confidence: 62%
“…Likewise, extracurricular activities, particularly when derived from a reflected and deliberated plan (Clark et al, 2015;Díaz-Iso et al, 2020), are generally linked to career resources, such as career exploration (Munson & Savickas, 1998;Potts, 2015), increased sense of competence derived from experience (Munson & Savickas, 1998), career agency (Munson & Savickas, 1998;Potts, 2015), skills development (Jackson & Bridgstock, 2020) and positive career prospects (Potts, 2015). Some research also suggests that social variables could influence career success, namely parental education (Erola et al, 2016;Tomlinson, 2017b), or being or not a first-generation student in higher education, with better career prospects for graduates with parents with higher education levels or social context (Eimer & Bohndick, 2021).…”
Section: Higher Education and Career Developmentmentioning
confidence: 99%
“…Studies at financially underprivileged college student groups (Hu et al, 2020) found that employability is a key factor that enables students to achieve career success regarding career choice and access to employment opportunities (Flores et al, 2017;Eimer and Bohndick, 2021). In China, financially underprivileged college students are identified via the document "Guidance on Carefully Identifying Students from Families with Economic Difficulties in Higher Education" (Education and Finance No.…”
Section: Introductionmentioning
confidence: 99%
“…In the modern education system, personal qualities can be linked to one’s engagement in activities, efforts and persistence, leading to ultimate success (Eimer and Bohndick, 2021; Rothwell et al, 2008). Personal qualities can also be related to the psychosocial perspective.…”
Section: Personal Upbringing Context and Employabilitymentioning
confidence: 99%